Neonatal BCG vaccination induces IL-10 production by CD4+CD25+T cells - AYDINER, ELİF; AKKOÇ, TUNÇ (WILEY, 2010)
To determine the optimal time of Bacillus Calmette-Guerin (BCG) vaccination for induction of Th1 immunity, we measured the interferon (IFN)-gamma and interleukin (IL)-10 secretion in purified protein derivative (PPD)-stimulated peripheral blood mononuclear cell (PBMC) cultures in newborns vaccinated at birth or 2nd month of life. Moreover, role of CD4+ CD25+ T cells was studied by depletion assay at 8th month. Nineteen term and healthy newborns were randomized into two groups: Group I composed of 10 newborns vaccinated with BCG at birth and the remaining 9 (group II) at 2nd month of life. PBMCs were isolated at birth, 2nd and 8th months of age, and PPD-stimulated IL-10, 5 and IFN-gamma secretion were assessed. The same measurements were repeated for IL-10 and IFN-gamma after the depletion of CD4+ CD25+ T cells at the 8th month. Children vaccinated at birth demonstrated higher PPD-stimulated IFN-gamma and IL-10 levels at 2 months of age when compared to non-vaccinated ones (p = 0.038 and p = 0.022, respectively), whereas at 8 months, no significant differences were detected between the two groups. Moreover, CD4+ CD25+-depleted T-cell cultures resulted in lower PPD-stimulated IL-10 levels in those vaccinated at birth when compared to non-depleted condition at the 8th month (p < 0.001). BCG at birth upregulated PPD-stimulated IFN-gamma secretion at the 2nd month and remained still detectable at 8 month after the vaccination, whereas those vaccinated at the 2nd month of life lacked that increase in IFN-gamma response at the same time-point. Furthermore, depletion assays suggest that CD4+ CD25+ T cells are involved in PPD-stimulated IL-10 secretion in response to BCG vaccination.
Keywords: Bacillus Calmette-Guerin; IL-10; IFN-gamma; children; purified protein derivative; MYCOBACTERIUM-TUBERCULOSIS INFECTION; CALMETTE-GUERIN-VACCINATION; BIRTH